Trouble of being - Murzicz, Paweł (Hybris, 2020)
The article shows that being in Martin Heidegger’s philosophy is not free from the language of values. German philosopher defined values as “objectified human purposes” and criticized traditional axiology for its separation of facts and values. Instead, he postulated “thinking of being”. Thus, I investigate the issue of criteria which could let us claim we do think being (Sein), not beings (Seiende), i.e. a metaphysical understanding of being. Next I go on to argue for the thesis that critique of values that Heidegger proposes, coming out of the notion of being which is not axiologically neutral. In later part I present arguments for the thesis that the concept of being could only emerge in the era of the will to power. Eventually I show how the philosophy of being essentially precludes the inclusion of the body into its discourse.